Prevalence and Predictors of Non-Compliance with Pharmacological Treatment in Diabetes : Non-Compliance with Pharmacological Treatment in Diabetes - Jehan, Ayesha Shah; Roshan, Summaya; Hussain, Shujaat; Maheen, Azka; Mahmood, Jawad; Zada, Akhtar (Pakistan Journal of Health Sciences, 2023)
Although the incidence of failure to comply to prescribe drugs is very varied, it may be the most frequent cause of suboptimal treatment results in diabetic patients. In the research region, there are little data on the extent of non-adherence to medicines and related causes. Objective: To determine the prevalence of non-adherence to medications in patients with diabetes and the factors leading to such practices. Methods: A descriptive study designed was chosen to evaluate 191 patients with diabetes enrolled at the department of medicine, combined military hospital, Nowshera, during the period May 2022 to May 2023. Non-adherence was confirmed clinically by taking history and biochemically by poor glycemic profile. SPSS version 24 was used to analyze the data. Results: The age of the patients ranged from 18 to 60 years. The mean age of the patients was 36.17 years with standard deviation 7.53. Age group 18 to 40 years comprised of 113 (59.2%) participants. The male participants were 129 (67.5%) in number. Non-adherence was observed in 86(45.5%) patients. Factors leading to non-adherence included financial constraints 32(37.2%), medications related to complications 16(18.6%). Conclusions: Diabetes patients often fail to comply with their prescribed prescriptions in the study region. To reduce disengagement among diabetes patients, public health programs should be reinforced.